2023
DOI: 10.32471/exp-oncology.2312-8852.vol-42-no-3.15068
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of purine dysmetabolism in gastric and pulmonary adenocarcinomas

Abstract: Summary. Aim: To study the state of purine metabolism in gastric (GAC) and pulmonary (PAC) adenocarcinomas and to assess its clinical and pathogenetic significance. Patients and Methods: One hundred and six male patients were examined, among whom were 63 subjects aged 34 to 79 suffering from GAC, and 43 subjects aged 24 to 76 suffering from PAC. In GAC, the ratio of the pyloric, corporeal and antral localization of the tumor and variant of overall gastric lesion accounted to 24:5:1:1; and that of the central a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In summary: although purine metabolism appears as a potentially interesting oncogenic pathway in TETs (that needs validation in independent cohorts of TETs), it remains enigmatic how the oxypurinol detected in aggressive TETs is generated and whether it is formed inside the tumors themselves. However, since purine metabolites are constituents of tumor-derived exosomes [65] and oxypurinol was recently detected in the blood of non-thymic cancer patients [66], future studies should address the levels of oyxpurinol in TETs and the blood of TET patients with fully monitored medication. Furthermore, future in vitro studies may eventually help to clarify the source of oxypurinol.…”
Section: General Versus Tet-specific Metabolitesmentioning
confidence: 99%
“…In summary: although purine metabolism appears as a potentially interesting oncogenic pathway in TETs (that needs validation in independent cohorts of TETs), it remains enigmatic how the oxypurinol detected in aggressive TETs is generated and whether it is formed inside the tumors themselves. However, since purine metabolites are constituents of tumor-derived exosomes [65] and oxypurinol was recently detected in the blood of non-thymic cancer patients [66], future studies should address the levels of oyxpurinol in TETs and the blood of TET patients with fully monitored medication. Furthermore, future in vitro studies may eventually help to clarify the source of oxypurinol.…”
Section: General Versus Tet-specific Metabolitesmentioning
confidence: 99%
“…3 In Y V Dumanskiy et al's article, purine metabolism disorder was observed in all gastric cancer patients in the experimental group, and the change in uric acid was more obvious in gastric cancer. 4 Therefore, the correlation between TAP and uric acid was analyzed, but the correlation between them was not statistically significant ( Table 5). The impaired balance between clotting and fibrinolysis leads to thrombus formation, and hypercoagulability is a risk factor for aggravating thrombus formation.…”
mentioning
confidence: 99%
“…Akin to PNP, HPRT has been used to activate the pro-drug deoxy-6-thioguanosine-5′-triphosphate which is responsible for cell apoptosis due to DNA mispairing (Yan et al, 2003). In a recent study, high levels of circulating uric acid in patients affected by gastric and pulmonary adenocarcinomas has been observed (Dumanskiy et al, 2020).…”
Section: Gbps and Cancermentioning
confidence: 99%